Pengaruh Karakteristik Komite Audit, Ukuran Kap, Dan Peran Internal Auditor Terhadap Ketepatan Waktu Penyampaian Laporan Audit - Mutia Rahmi; Efrizal Syofyan (Jurnal Eksplorasi Akuntansi, 2020)
The purpose of this study was to analyze the effect of audit committee characteristics, kap sizes, and internal auditor's role on accuracy of audit reporting time. The data used in this study are annual and financial reports in manufacturing companies listed on the indonesia stock exchange (idx) in the period 2014-2018. The method of taking data samples using purposive sampling method based on certain criteria. Based on the retrieval method obtained A sample of 240 companies. Hypothesis testing in this study uses Logistic regression analysis. The results show that the size of the audit committee, the financial expertise of the audit committee members, the size of the public accounting firm, the role of the internal auditor has no effect on accuracy of audit reporting time and the frequency of meetings of audit committee members has an effect on accuracy of audit reporting time.